The Impact of Varying Mixing Rates in a Surfactant-Free Fuel Emulsion Mixer on the Efficiency and Emissions of a Diesel Engine - Budi Santoso; Agus Sartomo; Ubaidillah Ubaidillah; Oki Muraza; Elliza Tri Maharani (Universitas Muhammadiyah Magelang, 2024)
The research focuses on water diesel emulsion (WDE), a topic that has captivated researchers for an extended period. While previous studies predominantly employed surfactants to enhance mixing efficiency, their non-economic feasibility in transportation logistics has prompted a shift in recent investigations. This study presents experiments utilizing a cost-effective WDE comprising 15% water and a mixer devoid of surfactants to investigate the impact of mixer blade rotation on engine performance, fuel consumption, and NOx emissions. NOx emission tests were conducted under a constant engine speed of 2,000 rpm and a 75% load (3,23 kW). The optimal brake-specific fuel consumption (BSFC) for the 15% WDE fuel occurred at a blade rotation speed of 3,000 rpm, resulting in a 1% power reduction (from 4,41 kW to 4,38 kW), a 13.3% decrease in BSFC (from 694,98 gr/kW.h to 602,52 gr/kW.h), and a 30% reduction in NOx emissions (from 54 ppm to 38 ppm). This discovery holds promise for future advancements in green energy applications within the transportation sector.